PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KONSTRUKTIVISME UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS SISWA SMA KELAS X - Rusiyanti, Rini Herlina (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2011)
Teaching learning process in math hasn’t been requiring student to construct their knowledge and to exercise their critical thinking. So need to develop constructivism instruction materials for exercise student’s ability in critical thinking. This research aim to: (1) Produce the valid and practice constructivism instruction materials to exercise student’s ability in critical learning, (2) Know effectiveness it to exercise student’s ability in critical learning. Instruction materials were developed in this research are plan learning, student worksheet and test of student’s ability in critical thinking. Development research methods are used by this research. The methods consist of analysis, design, evaluation and revision. Collecting data use Observation and test. Observation is used to know the student’s activity in teaching learning process and to know the teacher’s ability in learning constructivism approach management. Test is used to know the result of student’s ability in critical thinking after teaching learning process. Subjects in this research are students from the first semester in class X.7 at SMA Negeri 10, Palembang . The total subjects are 40 students. The conclusions are: 1. Instruction materials process development is for quadrate equivalence only that begins from analysis design, and than evaluation until revision. 2. Instruction materials prototype is developed, fulfill in valid and practice criteria also have effect potential. 3. Some aspects of student’s activity in learning process do not effective; because restructure (57.92 %) and review (55.00 %) just in enough category. The result learning test to evaluate student’s ability in critical thinking is 24.38. It means the student’s ability in critical thinking is good category. The final conclusion is constructivism instruction materials can practice to exercise student’s ability in critical thinking for math learning.DOI: 10.22342/jpm.5.2.598.